Psychological aspects associated with ACL rehabilitation and recurrence in football players: a systematic review - Luis Miguel Ramos Pastrana; José María Giménez Egido; Aurelio Olmedilla Zafra (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Although most football players recover good physical function after anterior cruciate ligament (ACL) surgery, some do not return to their sport or to the same pre-injury level, and there is a risk of recurrence. Therefore, this study aimed to examine research on psychological aspects of ACL rehabilitation and Return to Play (RTP), as well as their influence on possible recurrence in football and futsal players. The search was conducted using the Scopus, PubMed, WoS, CENTRAL databases, and grey literature sources DART-Europe and OpenGrey. A total of nine studies met the inclusion criteria. The results indicated as the most evaluated psychological factor the psychological readiness to RTP through the Anterior Cruciate Ligament Return to Sport After Injury (ACL-RSI). Likewise, psychological interventions in ACL-injured football players have positive effects on mood states, reduces pain perception, and fear reinjury, among others. Risk profiles for recurrence included vulnerability to stress and high psychological readiness to RTP. Therefore, psychological interventions should be incorporated into the rehabilitation process and screening to identify players at risk for poor outcomes or recurrences. Additional research would help to understand the influence of other variables or optimal levels of psychological readiness to RTP.